Families' experiences of supporting Australian veterans and emergency service first responders (ESFRs) to seek help for mental health problems. (5th June 2022) - Lawn, Sharon; Waddell, Elaine; Rikkers, Wavne; Roberts, Louise; Beks, Tiffany; Lawrence, David; Rioseco, Pilar; Sharp, Tiffany; Wadham, Ben; Daraganova, Galina; Van Hooff, Miranda
Abstract: The objective of this phenomenological study was to describe families' experiences of supporting veterans and emergency service first responders (ESFRs) (known also as public safety personnel) to seek help for a mental health problem. In‐depth semi‐structured open‐ended interviews were undertaken with 25 family members of Australian veterans and ESFRs. Fourteen participants were family members of police officers. Data were analysed thematically. Participants described a long and difficult journey of supporting the person's help‐seeking across six themes. Traumatic exposures, bullying in the workplace and lack of organisational support experienced by veterans/ESFRs caused significant family distress. Families played a vital role in help‐seeking but were largely ignored by veteran/ESFR organisations. The research provides a rich understanding of distress and moral injury that is experienced not only by the service members but is transferred vicariously to their family within the mental health help‐seeking journey. Veteran and ESFR organisations and mental health services need to shift from a predominant view of distress as located within an individual (intrapsychic) towards a life‐course view of distress as impacting families and which is more relational, systemic, cultural and contextual.